2(2f-3)=(-4f+2)

Simple and best practice solution for 2(2f-3)=(-4f+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2f-3)=(-4f+2) equation:



2(2f-3)=(-4f+2)
We move all terms to the left:
2(2f-3)-((-4f+2))=0
We multiply parentheses
4f-((-4f+2))-6=0
We calculate terms in parentheses: -((-4f+2)), so:
(-4f+2)
We get rid of parentheses
-4f+2
Back to the equation:
-(-4f+2)
We get rid of parentheses
4f+4f-2-6=0
We add all the numbers together, and all the variables
8f-8=0
We move all terms containing f to the left, all other terms to the right
8f=8
f=8/8
f=1

See similar equations:

| 1.2m+2.6=4.56 | | 7(x-2)+1=7x-12 | | 4^(z-2)=3.8 | | 93=30−e= | | 93=30−e+ | | 6x-8=32+2x | | 3(x-7)+7=3x-14 | | (4m-5)=180 | | 14(n+3=-28 | | 25x^2-75x-700=0 | | 7×x=84 | | 5-0.5x=11 | | 10y-43=2y+21 | | 7+3x=-11; | | 1/2(x-56)=37+7x | | 8x44=352 | | 3a^2-15a-18=0 | | (x-3)/7=-2; | | 2(3x-6)=6(3x+2) | | 4.94-0.08x=2.08+0.18x | | 7(y-2)+13=3(y+5); | | 2.08+0.18x=4.42 | | x-9=23;x=14 | | 4.63x=60 | | 5(t+25=875) | | x-4/3=-6 | | 7(y-2)+13=3(y+5) | | w−4=27 | | 2(x+3)-5(x-1)=-31; | | r−7=16 | | 60a+75=-50a+3 | | 2z/3+5=9; |

Equations solver categories